Survival of Xanthomonas phaseoli pv. phaseoli in the soil and the phyllosphere and rhizosphere of crops and weeds - do Nascimento, Daniele Maria [UNESP]; Oliveira, Letícia Rodrigues [UNESP]; Géa, Bianca Cristina Costa [UNESP]; de Melo, Luana Laurindo [UNESP]; Soman, José Marcelo [UNESP]; da Silva Júnior, Tadeu Antônio Fernandes [UNESP]; Maringoni, Antonio Carlos [UNESP] (Springer Nature, 2024)
Background and Aims: Common bacterial blight (CBB), caused by Xanthomonas phaseoli pv. phaseoli (Xpp), is a major disease affecting common bean production in Brazil. Understanding the survival of Xpp across various environments is essential for effective disease management. Methods: This study assessed Xpp survival under different environmental conditions, including variations in soil type and temperature, and the phyllosphere and rhizosphere of crops and weeds. Results: Xpp survived longest in clayey soils and at lower temperatures (15 °C). It exhibited prolonged survival in the phyllosphere of common beans (up to 70 days), while it survived minimally on non-host crops like cotton, maize, and soybean. Xpp survival was positively correlated with rainfall. In the rhizosphere, maximum survival occurred in pigeon pea (up to 42 days). Weeds showed varied survival rates, with the longest being 28 days in the phyllosphere of Cyperus rotundus, whereas other species supported the bacterium for 7 to 14 days. The maximum survival period of Xpp in the rhizosphere of weeds was 21 days, but in most species, it was only detected on the day the experiment was set up. Conclusion: Crop rotation with non-host crops such as cotton, maize, and soybean appears effective in reducing Xpp inoculum in fields. Managing weed populations is also crucial, as many can harbor Xpp, contributing to disease persistence. These findings are integral to developing integrated disease management strategies.
Keywords: Alternative host; Common bacterial blight; Common bean; Ecology; Phaseolus vulgaris